The petrogenesis of the Nelshoogte pluton: The youngest and most compositionally variable TTG pluton in the Barberton Granite-Greenstone Terrain - Matsumura, Risa (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014